How clay particulates affect flow cessation and the coiling stability of yield stress-matched cementing suspensions. Issue 16 (2nd April 2020) - Mehdipour, Iman; Atahan, Hakan; Neithalath, Narayanan; Bauchy, Mathieu; Garboczi, Edward; Sant, Gaurav
Abstract : Transition from closely-packed to fractally-architected structures with clay addition improves homogeneity and prevents local dewatering, thus enhancing coiling stability of layer-wise extruded cementing suspensions during 3D-printing. Abstract : The remarkable increase in the flow resistance of dense suspensions can hinder 3D-printing processes on account of flow cessation in the extruder, and filament fragility/rupture following deposition. Understanding the nature of rheological changes that occur is critical to manipulate flow conditions or to dose flow modifiers for 3D-printing. Therefore, this paper elucidates the influences of clay particulates on controlling flow cessation and the shape stability of dense cementing suspensions that typically feature poor printability. A rope coiling method was implemented with varying stand-off distances to probe the buckling stability and tendency to fracture of dense suspensions that undergo stretching and bending during deposition. The contributions of flocculation and short-term percolation due to the kinetics of structure formation to deformation rate were deconvoluted using a stepped isostress method. It is shown that the shear stress indicates a divergence with a power-law scaling when the particle volume fraction approaches the jamming limit; ϕ → ϕ j ≈ ϕ max . Such a power-law divergence of the shear stress decreases by a factor of 10 with increasing clay dosage. Such behavior in clay-containing suspensions arises from a decrease in the relative packing fraction ( ϕ / ϕ max ) and the formation of fractally-architected aggregates with stronger interparticle interactions, whose uniform arrangement controls flow cessation in the extruder and suspension homogeneity, thereby imparting greater buckling stability. The outcomes offer new insights for assessing/improving the extrudability and printability behavior during slurry-based 3D-printing process.